UNIT 13.22 STRAP PTM: Software Tool for Rapid Annotation and Differential Comparison of Protein Post‐Translational Modifications. Issue 1 (12th December 2013) - Spencer, Jean L.; Bhatia, Vivek N.; Whelan, Stephen A.; Costello, Catherine E.; McComb, Mark E.
Abstract: The identification of protein post‐translational modifications (PTMs) is an increasingly important component of proteomics and biomarker discovery, but very few tools exist for performing fast and easy characterization of global PTM changes and differential comparison of PTMs across groups of data obtained from liquid chromatography–tandem mass spectrometry experiments. STRAP PTM (Software Tool for Rapid Annotation of Proteins: Post‐Translational Modification edition) is a program that was developed to facilitate the characterization of PTMs using spectral counting and a novel scoring algorithm to accelerate the identification of differential PTMs from complex data sets. The software facilitates multi‐sample comparison by collating, scoring, and ranking PTMs, and by summarizing data visually. The freely available software (beta release) installs on a PC and processes data in protXML format obtained from files parsed through the Trans‐Proteomic Pipeline. The easy‐to‐use interface allows examination of results at protein, peptide, and PTM levels, and the overall design offers tremendous flexibility that provides proteomics insight beyond simple assignment and counting. Curr. Protoc. Bioinform . 44:13.22.1‐13.22.36. © 2013 by John Wiley & Sons, Inc.